Evaluation of Work-Based Learning Implementation through Internship at Vocational High Schools - Sugiharto Sugiharto; Yoto Yoto; Widiyanti Widiyanti (Belantika Pendidikan, 2021)
This article aims to identify and describe the evaluation of Work-Based Learning through an internship (WBL-Internship) in vocational high schools. This study is a multi-case study with a qualitative descriptive approach. The study took place at VHS 1 Bendo Magetan and VHS 1 Geger Magetan. Interviews, documentation, and observation studies were used to collect data. The results show that (1) The WBL-Internship consists of an industrial assessment and a school assessment. Academic and non-academic aspects are assessed. (2) The WBL-Internship assessment is based on attitude. (3) Reports on WBL-Internship activities are carried out by students periodically through reports and activity journals; (4) WBL-Internship certificates are given after all WBL-Internship activities are completed. (5) The enthusiasm and full support of all school and industry residents, as well as the limited number of industries for WBL-Internship, are supporting and inhibiting factors for WBL-Internship.